Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fceng.2022.850308
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Composting of Food Waste: A Perspective on Scientific Knowledge

Abstract: Composting has been demonstrated to be an effective and sustainable technology to treat a wide variety of organic wastes. A particular aspect of composting is the number of technological options that can be used, from full-scale plants to small composters. In this sense, the interest in composting at home or on a community scale is exponentially growing in recent years, as it permits the self-management of organic wastes and obtaining compost that can be used by the same producer. However, some questions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(65 reference statements)
1
9
0
1
Order By: Relevance
“…Agricultural activities can generate considerable amounts and variety of organic wastes such as crop refuse, fruit and vegetable refuse, tree trimming waste, animal manure, and poultry manure. Organic waste can be a major threat to the environment, e.g., air pollution, if not managed and treated properly [ 1 ]. When landfilled, organic waste undergoes biological degradation process releasing methane gas (CH 4 ), carbon dioxide (CO 2 ), hydrogen sulfide (H 2 S), nitrous oxide (N 2 O), and other gases in small amounts [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural activities can generate considerable amounts and variety of organic wastes such as crop refuse, fruit and vegetable refuse, tree trimming waste, animal manure, and poultry manure. Organic waste can be a major threat to the environment, e.g., air pollution, if not managed and treated properly [ 1 ]. When landfilled, organic waste undergoes biological degradation process releasing methane gas (CH 4 ), carbon dioxide (CO 2 ), hydrogen sulfide (H 2 S), nitrous oxide (N 2 O), and other gases in small amounts [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the physiochemical characteristics and mixing ratios of raw organic waste, being the feedstock for compost production, need to be assessed [ 38 , 42 ]. This is because the quality and portion of the feedstock used are the primary determinants of the composition and quality of the final compost, including its physiochemical properties [ 6 , 43 ] and its maturation time [ 1 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce these GHG emissions from MSW, different waste treatment technologies have been developed. These include waste composting technology reported by Sohoo et al (2021) and Sanchez (2022), and LFG energy projects reported in EPA (2021a, c) and Huang and Fooladi (2021). The incineration process was also reported in Moharir et al (2019), Gupta et al (2022) and Sohoo et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…These include waste composting technology reported by Sohoo et al. (2021) and Sanchez (2022), and LFG energy projects reported in EPA (2021a, c) and Huang and Fooladi (2021). The incineration process was also reported in Moharir et al.…”
Section: Introductionmentioning
confidence: 99%
“…La generación de residuos orgánicos está aumentando a nivel mundial y se deben desarrollar y optimizar estrategias para su impacto ambiental y costo (Rashwan et al, 2021). Ante tal problemática, las tecnologías de conversión altamente eficientes, económicas y respetuosas con el medio ambiente se vislumbran como la solución más acertada; en tal sentido, el compostaje tiene una alta capacidad para transformar diversos desechos orgánicos en un producto valioso para fines agrícolas, como medio de crecimiento hortícola para mejorar la estructura del suelo aumentando su contenido de materia orgánica y su fertilidad (Sánchez, 2022;Peralta et al, 2019).…”
Section: Introductionunclassified